Simulating pesticide transport from a sloped tropical soil to an adjacent stream - Kahl G. (2017)
Preferential flow from stream banks is an important component of pesticide transport in the mountainous areas of northern Thailand. Models can help evaluate and interpret field data and help identify the most important transport processes. We developed a simple model to simulate the loss of pesticides from a sloped litchi (Litchi chinensis Sonn.) orchard to an adjacent stream. The water regime was modeled with a two-domain reservoir model, which accounts for rapid preferential flow simultaneously with slow flow processes in the soil matrix. Preferential flow is triggered when the topsoil matrix is saturated or the infi ltration capacity exceeded. In addition, close to matrix saturation, rainfall events induce water release to the fractures and lead to desorption of pesticides from fracture walls and outflow to the stream. Pesticides undergo first order degradation and equilibrium sorption to soil matrix and fracture walls. The model was able to reproduce the dynamics of the discharge reasonably well (model efficiency [EF] = 0.56). The cumulative pesticide mass (EF = 0.91) and the pesticide concentration in the stream were slightly underestimated, but the deviation from measurement data is acceptable. Shape and timing of the simulated concentration peaks occurred in the same pattern as observed data. While the eff ect of surface runoff and preferential interflow on pesticide mass transport could not be absolutely clarified, according to our simulations, most concentration peaks in the stream are caused by preferential interflow pointing to the important role of this flow path in the hilly areas of northern Thailand. Copyright © 2010 by the American Society of Agronomy, Crop Science Society of America, and Soil Science Society of America. All rights reserved.